Volume Load-Induced Right Ventricular Failure in Rats Is Not Associated With Myocardial Fibrosis - Hagdorn, Quint A. J.; Kurakula, Kondababu; Koop, Anne-Marie C.; Bossers, Guido P. L.; Mavrogiannis, Emmanouil; van Leusden, Tom; van der Feen, Diederik E.; de Boer, Rudolf A.; Goumans, Marie-José T. H.; Berger, Rolf M. F. (Frontiers in Physiology, 2021)
1.1. Background Right ventricular (RV) function and failure are key determinants of morbidity and mortality in various cardiovascular diseases. Myocardial fibrosis is regarded as a contributing factor to heart failure, but its importance in RV failure has been challenged. This study aims to assess whether myocardial fibrosis drives the transition from compensated to decompensated volume load-induced RV dysfunction. 1.2. Methods Wistar rats were subjected to aorto-caval shunt (ACS, n=23) or sham (control, n=15) surgery, and sacrificed after 1, 3 or 6 months. Echocardiography, RV pressure-volume analysis, assessment of gene expression and cardiac histology were performed. 1.3. Results At 6 months, 6/8 ACS-rats (75%) showed clinical signs of RV failure (pleural effusion, ascites and/or liver edema), whereas at 1 and 3 month(s), no signs of RV failure had developed yet. Cardiac output has increased two- to three-fold and biventricular dilatation occurred, while LV ejection fraction gradually decreased. At 1 and 3 month(s), RV end-systolic elastance (Ees) remained unaltered, but at 6 months, RV Ees had decreased substantially. In the RV, no oxidative stress, inflammation, pro-fibrotic signaling (TGFβ1 and pSMAD2/3) or fibrosis were present at any time point. 1.4. Conclusions In the ACS rat model, long-term volume load was initially well tolerated at 1 and 3 month(s), but induced overt clinical signs of end-stage RV failure at 6 months. However, no myocardial fibrosis or increased pro-fibrotic signaling had developed. These findings indicate that myocardial fibrosis is not involved in the transition from compensated to decompensated RV dysfunction in this model.